2009
DOI: 10.1063/1.3213358
|View full text |Cite
|
Sign up to set email alerts
|

X-ray ablation of hyaluronan hydrogels: Fabrication of three-dimensional microchannel networks

Abstract: We present a simple and highly versatile protocol for polymer ablation: hard x-ray irradiation makes it possible to rapidly depolymerize hyaluronan hydrogels and fabricate three-dimensional network of microchannels. Photodynamic and photochemical analyses show that x-ray irradiation directly cleaves the polymer backbone and the total dose controls the degradation kinetics. This nonthermal ablation protocol may offer opportunities for processing organic polymers and biological materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…21 Besides, fabrication routes such as X-ray ablation, layer-by-layer printing were also used for 3D microstructure prototyping. 22 Recently, a novel self-folding route was reported for fabrication of real 3D microstructures from precreated 2D micropatterns. [23][24][25] Using self-assembly, 2D cruciform structures with porosity could be transformed into 3D microcontainers with porous walls, 26,27 which shows great potential for cell encapsulation and separation towards microfluidic appliations.…”
Section: Introductionmentioning
confidence: 99%
“…21 Besides, fabrication routes such as X-ray ablation, layer-by-layer printing were also used for 3D microstructure prototyping. 22 Recently, a novel self-folding route was reported for fabrication of real 3D microstructures from precreated 2D micropatterns. [23][24][25] Using self-assembly, 2D cruciform structures with porosity could be transformed into 3D microcontainers with porous walls, 26,27 which shows great potential for cell encapsulation and separation towards microfluidic appliations.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Here our results of PDMS demonstrate that X-ray irradiation is a highly efficient and feasible protocol for surface modification through PDMS ablation. The X-ray-induced ablation enables one not only to oxidize the PDMS surface (hydrophilicity) but also to deposit the ablated PDMS (hydrophobicity) on other hydrophilic surfaces.…”
mentioning
confidence: 78%
“…177 Such microchannels, embedded in a hyaluronan hydrogel, has also been by using hard x-ray irradiation. 178 In another approach, hydrogel mediated partitioning of microchannels has been used to create tunable 3-D cellular microenvironment. 179 To stretch the scope of applicability even further, a research group has recently reported a method to fabricate biofunctionalized polyethylene glycol hydrogel microchannels with adjustable circular cross-sections.…”
Section: Effect Of the Microconfinementmentioning
confidence: 99%